Analisis SWOT Sebagai Upaya Peningkatan Evaluasi Internal Lingkungan Perusahaan dalam Mencapai Keunggulan Bersaing - Hesti Kusumaningrum; Muftiatul Husna; Clarista Anindiya (Al-Faiza : Journal of Islamic Education Studies, 2024)
SWOT analysis is widely used as a tool for analyzing a company's internal and external environment. This analysis is based on the idea that effective strategies minimize weaknesses and threats if used correctly, this simple idea has a significant impact on how the strategy is created. Developing an appropriate conceptual model to determine company strategy and identifying optimal areas using SWOT (Strengths, Weaknesses, Threats, Opportunities) and QSPM (Quantitative Strategic Planning Matrix) techniques will help further company strategy and build a conceptual model to find the optimal area. Conversely, a SWOT analysis also determines which components will help the company achieve its goals, which groups face challenges, and what will dominate or be minimized to achieve the desired results. With rapid changes, the challenges of the 40th Industrial Era can provide entrepreneurs with both opportunities and threats. Therefore, a company must have an appropriate competitive strategy to achieve the goal of increasing profit or profit by one way, namely increasing marketing. One way to understand the right strategy for a company is to carry out a SWOT analysis.